HUBUNGAN TINGKAT DEPRESI DENGAN GANGGUAN MENSTRUASI PADA MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS LAMBUNG MANGKURAT - Noor, Meitria Syahadatina; Yasmina, Alfi; Rahmi, Yulida (Universitas Lambung Mangkurat, 2014)
Menstruation is periodical and cyclically hemorhagic from uterus with endometrium release (deskuamasi). Menstruation cycle varying on every women, estimated cycle length ranging from 25 to 35 days with average 28 days. Menstruation long usually 5 to 7 days, but some women have unregular cycle (disorder) and this can be an indication of vertility problem . unregular menstruation cycle caused by psychical trouble, as depression. This study aim to knowing Relation of depression state with menstruation disorder in at medical faculty lambung mangkurat university's student. This study is a survey analitic research with prospective approach. Sampling do with non-probability sampling with purposive sampling.Â Sample on this study is medical faculty lambung mangkurat university's students, sample that include inclusion criteria 21 student. Relation of depression state with disorder menstruation in this study measured with quesioner. The result is analyzed using chi square and kolmogorov-smirnov with confident level 95% (Î±= 0,05). this study's result show that light depressi 2 student, menstruation disorder monoragia 2 student, hipermenorea 2 student, oligomenora 3 student and polymenorea 2 student. Based on statistic analyz found significant value 1,000; 1,000; 0,862 (p < 0,05), then can concludedÂ there is not be a significant relation between depression state with disorder menstruation in at medical faculty lambung mangkurat university's students.Â Key words: Disorder menstruation, depression state, student